Effect of Administration of Red Fruit (Pandanus conoideus L.) Extract in TNF-α, Microvessels Density Expression and Endometriosis Implant Area in Endometriosis Mice Model - Sutrisno Sutrisno; Hendra Brahmantyo Ratsamanda; I Wayan Arsana Wiryasa; Steven Christian Susianto; Burhan Mahendra Kusuma (Asian Journal of Health Research, 2022)
Introduction: The prevalence of endometriosis in women of reproductive age was still high. A previous study showed that the red fruit (Pandanus conoideus L.) extract consisted of alpha-tocopherol and beta carotene as antioxidants that could potentially be an alternative treatment in endometriosis. This study aimed to determine the effect of Red Fruit Extract Administration on the expression of TNF-α, microvessels density (MVD), and the area of endometriosis implant in endometriosis mice model. Methods: This was an experimental study with a randomized post-test control group design only applied to the endometriosis mice model and conducted in the Veterinary Faculty of Medicine Airlangga University, Surabaya. Twenty-eight endometriosis model mice were randomly divided into two groups. The control group (K) received CMC Na 5% for 14 days, and the treatment group (P) was given Red Fruit extract of 0,05 ml/day for 14 days. After day 28, mice were sacrificed, and immunohistochemical analysis was performed for TNF-α, microvessel density (MVD), and measured for endometriosis implant area. A T-test was used to analyze the comparison between groups. Results: Mean TNF-α, microvessel density, area of endometriosis implant in treatment group were 1,56±0,87, 1,26±0,48, 13,24±4,08, respectively. There was a statistically significant difference in TNF-α expression, MVD development, and area of endometriosis implant between the treatment and control groups (p<0.05). Conclusion: There was decreased expression of TNF-α, development of microvessel density, and area of endometriosis implant in endometriosis mice model given red fruit extract and proved to have potential effect as endometriosis therapy.